2016
DOI: 10.1111/aas.12773
|View full text |Cite
|
Sign up to set email alerts
|

Transversus abdominis plane block or intravenous lignocaine in open prostate surgery: a randomized controlled trial

Abstract: Our study suggests that TAP block and intravenous lignocaine do not improve the post-operative analgesia provided by systematic administration of paracetamol after open prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…The obtained results are in line with the findings of 1 recently published trial that compared the effect of systemic lidocaine and TAP-block on postoperative pain after open prostate surgery showing no significant differences in postoperative opioid consumption for systemic lidocaine and TAP-block. 23 The reasons why the QL-block and systemic lidocaine had comparative analgesic effects in our study are speculative.…”
Section: Discussionmentioning
confidence: 77%
“…The obtained results are in line with the findings of 1 recently published trial that compared the effect of systemic lidocaine and TAP-block on postoperative pain after open prostate surgery showing no significant differences in postoperative opioid consumption for systemic lidocaine and TAP-block. 23 The reasons why the QL-block and systemic lidocaine had comparative analgesic effects in our study are speculative.…”
Section: Discussionmentioning
confidence: 77%
“…To date, three studies have investigated the efficacy of transversus abdominis plane blocks for open prostatectomy. [212][213][214] Two of the three trials could not detect significant benefit associated with lateral transversus abdominis plane blocks. Thus, we do not suggest their use for open prostatectomy.…”
Section: Prostactectomymentioning
confidence: 93%
“…The 2018 update [17] incorporated 23 new trials, taking the total number of studies to 68. Out of these, 22 examined open abdominal surgery and 20 laparoscopic surgery, including (in addition to a new study in the 2015 version [63]), a further seven trials [64–70] measuring pain at 24 h. The authors also noted that a number of studies reported small variances, and added the novel methodological feature of 95% prediction intervals. These provide an index of dispersion (based on the SD) that suggests how widely the mean effects vary across populations; reporting a prediction interval in addition to the summary estimate and CI illustrate what range of true mean effects might be expected in future settings, and is also helpful in the clinical interpretation of heterogeneity.…”
Section: Is Intravenous Lidocaine Effective In the Treatment Of Postoperative Pain?mentioning
confidence: 99%